Co-Rooming Accounts for Socioeconomic Disparities in Infant Sleep Quality among Families Living in Urban Environments - Morgan A. Finkel; Sonya V. Troller-Renfree; Jerrold S. Meyer; Kimberly G. Noble (MDPI AG, 2022)
Poor infant sleep quality is associated with negative maternal and infant health outcomes. This study measures socioeconomic disparities in infant sleep quality, and assesses whether child sleep location and maternal stress mediate associations between socioeconomic status (SES) and infant sleep quality. The study includes 86 socioeconomically diverse, mother-infant dyads living in an urban area with infants aged 6-12 months. Mothers reported socioeconomic demographics, infant sleep quality (Brief Infant Sleep Questionnaire) and maternal subjective stress (Perceived Stress Scale). Maternal objective stress was measured via hair cortisol concentration (HCC). The associations among SES, infant sleep quality, infant co-rooming, and maternal stress were assessed. Infants from families with lower income-to-needs (ITN) ratios had poorer infant sleep quality. The association between familial ITN and infant sleep quality was mediated by whether the child co-rooms with parents. Maternal perceived stress was independently associated with infant sleep quality, but HCC was not associated with infant sleep quality.